Conductive polypyrrole-carboxymethyl cellulose-titanium nitride/carbon brush hydrogels as bioanodes for enhanced energy output in microbial fuel cells. (1st August 2020) - Wang, Yuyang; Wen, Qing; Chen, Ye; Li, Wei
Abstract: Microbial fuel cells (MFCs) are a renewable energy supply that converts chemical energy stored in wastewaters directly into electrical energy using microorganisms as biocatalysts. Modifications of anode materials are one way to enhance MFC energy output performance. Conducting polymer hydrogels, a unique class of materials having the advantageous features of both hydrogels and organic conductors, display excellent electrochemical properties due to their intrinsic porous structure. In this work, a conductive and self-supporting polypyrrole-carboxymethyl cellulose-titanium nitride/carbon brush hydrogel (PPy-CMC-TiN/CB) as a bioanode was prepared for enhancing the energy output of MFCs. Scanning electron microscopy showed that the PPy-CMC-TiN/CB composite anode had a three-dimensional macroporous structure that had a large specific surface area, providing more places for the attachment and growth of microorganisms. The maximum power density of the MFC with the PPy-CMC-TiN/CB hydrogel anode (14.11W m −3 ) was 4.72 times larger than that of the blank CB anode. During the charging-discharging test, the average peak current density of MFCs equipped with the PPy-CMC-TiN/CB hydrogel anode was 10.12 times higher than that of CB anode. The excellent results were attributed to the synergistic effect of PPy, CMC, and TiN, resulting in a highly active electrochemical anode. Highlights: A biocompatible and conductive PPy-CMC-TiN/CB hydrogel anode was prepared. The power of the modified anode was 4.72 times higher than that of the bare anode. An integration of electricity generation and energy storage in MFC. The synergistic effect of PPy, CMC and TiN improved the performance the MFC.